Motherless Brooklyn - Lethem, Jonathan, 1964- (Faber and Faber, 2000)
Lionel Essrog, a.k.a. the Human Freakshow, is a victim of Tourette's syndrome (an uncontrollable urge to shout out nonsense, touch every surface in reach, rearrange objects). Local tough guy Frank Minna hires the adolescent Lionel and three other orphans from St Vincent's Home for Boys and grooms them to become the Minna Men, a fly-by-night detective-agency-cum-limoservice. Then one terrible day Frank is murdered, and Lionel must become a real detective.